Analysis of the effectiveness of countering doping in sports in the framework of medical and biological support for athletes of national teams - A. A. Derevoedov; A. V. Zholinsky; V. S. Feshchenko; I. T. Vykhodets; A. A. Pavlova (National Electronic Information Consortium (NEICON), 2023)
Objective: analysis of the effectiveness of combating doping in sports in the process of medical and biological support of athletes forming the national teams of the Russian Federation, and determining its ways.Materials and methods: based on the reports of anti-doping organizations for 2017-2022, sociological studies of the prevalence of doping in sports and therapeutic use structures, a retrospective analysis of the dynamics of the main indicators reflecting the directions of various doping encounters was carried out.Results: a significant discrepancy was revealed between the assessment of the prevalence of anti-doping rule violations based on the results of sociological surveys and the results of laboratory anti-doping studies.A significant positive dynamic of approval of therapeutic use exemptions, which allowed doubling the share of positive decisions of anti-doping organizations is shown.The main directions of improving anti-doping work in the process of carrying out medical and biological support measures are determined.